2021
DOI: 10.3934/neuroscience.2021022
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis in the management of PTSD: a systematic review

Abstract: Introduction Existing reviews exploring cannabis effectiveness have numerous limitations including narrow search strategies. We systematically explored cannabis effects on PTSD symptoms, quality of life (QOL), and return to work (RTW). We also investigated harm outcomes such as adverse effects and dropouts due to adverse effects, inefficacy, and all-cause dropout rates. Methods Our search in MEDLINE, EMBASE, PsycInfo, CINAHL, Web of Science, CENTRAL, and PubMed database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 60 publications
0
19
1
Order By: Relevance
“…In a sharp difference to opioid-based drugs, nabiximols were shown to be well tolerated in clinical trials with very mild side effects, such as dizziness or disorientation with no significant adverse effects on cognition [28][29][30]. Although mostly based on non-randomized studies with no comparators, a recent systematic review also shows that using cannabis by patients with post-traumatic stress disorder (PTSD) improves pain and sleep and is associated with reduced overall PTSD symptoms and reports of a better quality of life [31,32]. Likewise, cannabis provides a beneficial intervention for reducing inflammation-related morbidity in acquired immunodeficiency syndrome (AIDS) patients [33], also improving muscle and nerve pain, and may also assist with depression [34][35][36].…”
Section: Neuropathic Neurological and Hiv-related Symptomsmentioning
confidence: 99%
“…In a sharp difference to opioid-based drugs, nabiximols were shown to be well tolerated in clinical trials with very mild side effects, such as dizziness or disorientation with no significant adverse effects on cognition [28][29][30]. Although mostly based on non-randomized studies with no comparators, a recent systematic review also shows that using cannabis by patients with post-traumatic stress disorder (PTSD) improves pain and sleep and is associated with reduced overall PTSD symptoms and reports of a better quality of life [31,32]. Likewise, cannabis provides a beneficial intervention for reducing inflammation-related morbidity in acquired immunodeficiency syndrome (AIDS) patients [33], also improving muscle and nerve pain, and may also assist with depression [34][35][36].…”
Section: Neuropathic Neurological and Hiv-related Symptomsmentioning
confidence: 99%
“…Literature reviews from the past two years that have examined the effectiveness of cannabis on PTSD symptoms count a small number of heterogeneous studies (open-label, longitudinal, and retrospective studies) with methodological problems and many limitations ( 28 , 29 ). To date, there were only two randomized, controlled clinical trials for PTSD patients.…”
Section: Introductionmentioning
confidence: 99%
“…The first used the synthetic cannabinoid nabilone ( 30 ), and the second used smoked cannabis but for only three weeks and was underpowered to detect significant differentiation from placebo ( 31 ). The conclusions of the few systematic reviews examining the effectiveness of cannabis on PTSD symptoms are that cannabis and synthetic cannabinoids may have a role in the treatment of PTSD, but there is currently limited evidence regarding their safety and efficacy ( 28 , 29 ). Therefore, additional research is needed to better understand the effectiveness and safety of cannabis in the treatment of PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…A third review delves into the effectiveness of cannabis on PTSD symptoms, the quality of life of patients undergoing this therapy and reintegration into the world of work, probing the various side effects of the therapy (8). Finally, the latest review found has set itself the goal of determining the clinical and therapeutic potential of cannabis and synthetic cannabinoids for PTSD.…”
Section: Introductionmentioning
confidence: 99%